(untitled) (International Journal of Engineering and Computer Science, 2014)
Web Structure Mining deals with the hyperlink structure of the document in the web. The various Web Structure Mining algorithm are page rank, weighted page rank, hyper induced topic search(HITS),Link Editing, Topological Utility Frequency Mining. The study focuses on the page rank algorithm. The following section describes the page rank algorithm structure, computation, problems, pros and cons.